STANDAR OPERASIONAL PROSEDUR ADMINISTRASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN ENREKANG - Usman, Muh Alfian; Abdi, Abdi; Arfah, Sitti Rahmawati (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out the Standard Operating Procedures (SOP) of Population Service Administration at the Population and Civil Registry Office of Enrekang Regency. This study used qualitative research. This study used descriptive research. The data sources were Primary data and secondary data, the data collection techniques used observation, interview, documentation. Then, data Analysis Techniques in this study used data reduction, data presentation and conclusion. The results of this study about Standard Operational Procedures for Population Administration at the Department of Population and Civil Registration of Enrekang Regency using 7 indicators, namely Ease and clarity, efficiency and effectiveness, harmony within, harmony within, dynamic, orientation, legal compliance and legal certainty, where from the results of the study showed that the implementation of the SOP had been implemented properly and the employees had carried out their duties in accordance with the SOP that had been applied.